Corporate Governance Regulation and Technology: Indonesia’s Way to Move Forward (Journal of Private and Commercial Law, 2020)
The study aims to analyze the regulation and implementation of corporate governance in Indonesia, and extend it to the beneficial utilization of technological advancements in the legal field that can be applied to developing Indonesian good corporate governance implementation. The analysis will be carried out through a normative-juridical method, utilizing the statute approach in which relevant laws and regulations are enquired into, supported by the existing literatures and academic papers. The paper looks into the weaknesses of the currently prevailing corporate governance regulatory regime, followed by the possible use of technology to develop Indonesia’s corporate governance implmenetation. The study finds that the drawbacks of Indonesian corporate governance legal regime include the needs for stronger and stricter regulation such as in relation to the requirement for affiliation for Board of Directors and Board of Commissioners, as well as minority shareholders protection linked to an equitable decision making process in a General Meetings of Shareholders. Further, technological advancements can be used for the betterment of corporate governance implementation in Indonesia, such as in terms of automation of document filing, submission and reporting in addition to other practical online and digital means which include the eASY.KSEI system as the official online General Meetings of Shareholders platform for public companies that has been tested during the recent COVID-19 pandemic situation.